A conceptual framework of performance assessment for private finance initiative projects in Malaysia - Nor Suzila Lop; Kharizam Ismail; Haryati Mohd Isa (Penerbit Universiti Kebangsaan Malaysia, 2018)
Private Finance Initiative (PFI) is one of the procurement methods that has been applied widely in the global construction market including Malaysia. PFI is an alternative procurement which is viewed as restructuring the previous privatisation concept in delivering value for money (VFM) for Malaysian public infrastructure. Among the restructuring efforts in the privatisation is specifying the standard assessment of private concessionaires’ performance through the execution of key performance indicators (KPIs). The assessment is practically benchmarked against the government’s standard. However, in Malaysia, lack of an effective KPIs is identified as one of the core criticisms for measuring the PFI projects performance. Therefore, two objectives are established which are; to investigate the implementation of various PFI performance measurement models across the globe to measure the performance and how these models can be adopted within the PFI in Malaysians. Finally, a conceptual framework is proposed for measuring performance of PFI projects in Malaysia. The outcomes of this paper can serve as a theoretical base for the development of an effective performance measurement tool for monitoring and measuring PFI projects performance in Malaysia.